If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3k + -2 + 4k = -23 Reorder the terms: -2 + 3k + 4k = -23 Combine like terms: 3k + 4k = 7k -2 + 7k = -23 Solving -2 + 7k = -23 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7k = -23 + 2 Combine like terms: -2 + 2 = 0 0 + 7k = -23 + 2 7k = -23 + 2 Combine like terms: -23 + 2 = -21 7k = -21 Divide each side by '7'. k = -3 Simplifying k = -3
| 33=3x-9 | | 5x+78=48+3x | | X+-2=10 | | x+3(-2)=1 | | 5x-3/x-1=3/2 | | 53+8x-4=90 | | 6+3x-2x=9 | | f(n)=2(3) | | .25x+78=48-3x | | 48/9=72/h | | x-1.4=6.0 | | -3y-4y-12y= | | 3x+9-7(x+1)=4x+7 | | (15x)/5 | | 15x-7x=48 | | .25x-5x=2x+43 | | -4i-6j= | | (6x-18)(3x+12)=0 | | -6(4p+3)-34=4(2p+3) | | 2/3×4/5=1/3÷m | | 4x+24+x=29 | | 1=2a-2a | | h=-.2t^2+86t+4 | | -2-4(2x+1)=5(3x-2) | | y=13/5x | | X-9+2x=-3 | | 5x-11+3x=29 | | f(n)=3f(n-1) | | 7x-40=2x+5 | | 10x+14=6x+30 | | 1/3(3x-6)=5x-3-2x | | 6x-43=2x-67 |